Wstępne podsumowanie badań zaburzeń mowy u dzieci w wieku przedszkolnym z dysfunkcją fazy połykania i oddychania - Malicka, Izabela (Logopedia Silesiana, 2014)
Preliminary summary of researches dealing with disorders of speech regarding children of pre-school age with the dysfunction of swallowing and breathing In the article the author presents the results of initial research of disorders of the oral phase of swallowing and breathing in children of preschool age. She points out the relationship between breathing, swallowing and the development of child’s phonetic and phonological system. The aim is to identify the existing difficulties of the patient to plan speech-therapy with the focus on achieving proper articulation.